Too levered for Pigou: Carbon pricing, financial constraints, and leverage regulation - Robin Döttling; Magdalena Rola-Janicka (European Central Bank (ECB), 2023)
We analyze jointly optimal carbon pricing and leverage regulation in a model with financial constraints and endogenous climate-related transition and physical risks. The socially optimal emissions tax is below the Pigouvian benchmark (equal to the direct social cost of emissions) when emissions taxes amplify financial constraints, or above this benchmark if physical climate risks have a substantial impact on collateral values. Additionally introducing leverage regulation can be welfare-improving only if tax rebates are not fully pledgeable. A cap-and-trade system or abatement subsidies may dominate carbon taxes because they can be designed to have a less adverse effect on financial constraints.
Keywords: D62; G28; G32; G38; H23; 330; Pigouvian tax; carbon pricing; financial constraints; climate risk; financial regulation